Clinical Analysis of Sphenoid Sinus Mucocele With Initial Neurological Symptoms. Issue 8 (25th July 2019) - Chen, Keyang; Cao, Yungang; Wu, Jianbin; Xiang, Haijie; Huang, Xiu‐Feng; Chen, Bobei
Abstract : Background and Objectives: Neurological manifestations associated with sphenoid sinus mucocele (SSM) are easily misdiagnosed due to nonspecific symptoms. The objective is to analyze and report the clinical features of SSM presenting with neurological manifestations, to allow an earlier diagnosis and more timely intervention for this disease. Methods: This was a retrospective cross‐sectional study including 19 patients. The detailed clinical information of 19 patients with the initial symptom of neurological manifestations caused by SSM presenting at the Second Affiliated Hospital of Wenzhou Medical University between January 2000 and May 2018 were retrospectively analyzed. Collected data including symptoms, signs, neuroimaging, and pathologic diagnoses. Results: There were eleven males and 8 females, and their ages ranged from 23 to 71 years. Headache was the most frequent symptom, in 12 of the 19 patients presenting as the initial symptom. The visual disturbance included visual loss (4/19), diplopia (3/19), and another patient had both visual loss and diplopia. Neurophysical examination found that 4 patients presented with oculomotor nerve palsy, 4 patients had optic nerve or abducens nerve palsy, and 1 patient had optic neuropathy, oculomotor nerve palsy and abducens nerve palsy simultaneously. All patients underwent endoscopic surgery and had postoperative clinical symptom improvement. Conclusions: Headache is the most common symptom of SSM and should be on the differential diagnosis of patients presenting with headache, even if in isolation. The results suggest that CT and MRI are the best tools in diagnosis of SSM and endoscopic sphenoidotomy is a safe and effective method in the treatment of SSM.